Improving the quality of business processes with Financial information systems - Kurnia Ekasari; Nurafni Eltivia; Bagas Brian Pratama; Nur Azizah (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2022)
This study aims to analyze the impact of the application of information technology on the company's business processes, especially in the financial administration process. The analysis technique adapts the Miles and Huberman model using the Business Process Management (BPM) framework. The BPM framework was chosen because it can provide a more comprehensive measurement in assessing the implementation of the use of information technology in the financial administration process. There are three research stages: data reduction from documentation, questionnaires, and interviews. Then the data is presented using the matrix and the Business Process Management Notation (BPMN) model. Moreover, the last is the conclusion formulation stage with evaluation using the Business Process Improvement (BPI) framework. This study shows that applying financial information systems in companies has benefits in simplifying processes, saving cycle time, preventing errors, increasing standardization, and improving large-scale processes by automating company processes.